Tetrafuroyl alpha-methyl-d-glucoside-synthesis and properties - Manuel, Marissa Formento; Gomez, Lilly K. (Quezon City Department of Chemistry, College of Liberal Arts, University of the Philippines Diliman, 1960)
An ester of alpha-methyl-d-glucoside, which the author, after checking the available literature, presumes to be a new compound, was synthesized from alpha-methyl-glucoside and furoyl chloride, in pyridine, at 0°. The solubility of the ester in organic compounds, its melting point, its saponification equivalent, its molecular weight and its carbon and hydrogen content were determined. The ester is believed to be tetrafuroyl alpha-methyl-d-glucoside (C27H22O14).
Thesis (Bachelor of Science in Chemistry)--University of the Philippines Diliman, April 1960.
Keywords: Sugar esters; Esters